Utility of Certain Nucleophilic Aromatic Substitution Reactions for the Assay of Ethamsylate in its Dosage forms and in Presence of its Degradation Product - Belal, F.; EL-Din, M. Sharaf; Tolba, M. M.; Alaa, H. (JOURNAL OF ADVANCES IN CHEMISTRY, 2011)
The study represents the first report on the development of spectrophotometric methods for determination of ethamsylate (EST) in the presence of hydroquinone as an impurity and/or acidic degradation product. The proposed methods are based on the reaction of EST through it,s secondary amino group either with 1,2-naphthoquinone-4-sulphonate sodium (NQS) at pH 10.7 or 2,4-dinitrofluorobenzene (DNFB) at pH 9.3 to form orange and yellow colored reaction products peaking at 478 and 387 nm for methods (I) and (II), respectively. The different experimental parameters affecting the development and stability of the reaction products in methods (I) and (II) were carefully studied and optimized. The absorbance-concentration plots were rectilinear over the concentration ranges of 2-30 and 2-14 µg mL−1 for methods (I) and (II), respectively. The lower detection limits were 0.13 and 0.19 µg mL−1 and the lower quantitation limits were 0.44 and 0.63 µg mL−1 for methods (I) and (II), respectively. Both methods were successfully applied to commercial ampoules and tablets.